PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS V UPTD SD NEGERI 1 SAMALANGA - Rahmah, Nailul; Nurmina; Agustisa, Mutia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study is based on the low writing skills of fifth-grade students at UPTD SD Negeri 1 Samalanga, which are caused by learning activities that do not actively engage students and the use of monotonous teaching methods. This study aims to improve students' descriptive writing skills, identify teacher and student activities, and determine students' responses through the implementation of the Think Talk Write (TTW) learning model in the fifth grade of UPTD SD Negeri 1 Samalanga. This study employed a qualitative approach using Classroom Action Research (CAR) consisting of two cycles. The participants were 30 fifth-grade students of UPTD SD Negeri 1 Samalanga. Data were collected through tests, observations, and questionnaires to determine students' responses.The results showed that the implementation of the Think Talk Write (TTW) learning model improved students' descriptive writing skills. In Cycle I, 17 students achieved mastery learning with a percentage of 56.67%, while in Cycle II, the number increased to 26 students with a percentage of 86.66%. Teacher and student activities also improved during the implementation of the TTW model. Teacher activity increased from an average of 80% in Cycle I to 97% in Cycle II, while student activity increased from 75% in Cycle I to 95.5% in Cycle II. In addition, students' responses to learning descriptive writing through the TTW model across the two cycles were generally categorized as very good. Based on these findings, it can be concluded that the implementation of the Think Talk Write (TTW) learning model successfully improved students' descriptive writing skills in each cycle and encouraged more active and participatory learning.